2021
DOI: 10.1002/cbin.11739
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects H9c2 cardiomyoblasts from oxygen‐glucose deprivation and reperfusion‐induced injury by inhibiting Rac1/JNK/Foxo3a/Bim signaling pathway

Abstract: Melatonin has been shown to protect against ischemia/reperfusion (I/R)‐induced myocardial injury, however, the precise molecular mechanisms have not been fully clarified. The present study was aimed to investigate whether inactivation of Rac1/JNK/Foxo3a/Bim signaling pathway is responsible for the protective effect of melatonin on I/R‐induced myocardial injury. Our results showed that Foxo3a downregulation contributed to the protective effect of melatonin on OGD/R‐induced injury of H9c2 cardiomyoblasts. Melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In a follow-up study, we used qPCR for different treatment groups to verify differential expression of Rac1, the target gene of miR125b-5p. Some studies showed that Rac1 activation can aggravate myocardial injury (Wang et al, 2022). Rac1 can activate ERK/P38MAPK signaling pathway (Zhu et al, 2009).…”
Section: Figurementioning
confidence: 99%
“…In a follow-up study, we used qPCR for different treatment groups to verify differential expression of Rac1, the target gene of miR125b-5p. Some studies showed that Rac1 activation can aggravate myocardial injury (Wang et al, 2022). Rac1 can activate ERK/P38MAPK signaling pathway (Zhu et al, 2009).…”
Section: Figurementioning
confidence: 99%